Leadership Insights: Enhancing Educator Quality in Madrasah Education - Meisuri, Meisuri; Dermawan, Oki; Patimah, Siti; Makbuloh, Deden; Subandi, Subandi (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
The quality of good educators can be supported by several factors and indicators. One of the factors is the leadership of the madrasa principle, where a madrasa principle must have the ability to influence, direct, and mobilize teaching staff to achieve the goals of an educational institution. The results of pre-research at MTs 1 Bandar Lampung show that there are still several teaching staff who still need to meet the criteria for quality teaching staff. The problem formulation is whether there is an influence of the leadership of the madrasa principle on the quality of educators at MTs 1 Bandar Lampung. The aim of this research is to determine the influence of the leadership of the madrasa principle on the quality of educators at MTsN 1 Bandar Lampung. The method used in this research is a quantitative method with a field research approach. Meanwhile, the population in this study was 43 responses from MTsN 1 Bandar Lampung teaching staff. And the sample used is the Slovin Technique. The data collection technique uses a questionnaire with a Likert scale. Data analysis techniques use normality tests, homogeneity tests, and linearity tests. Meanwhile, hypothesis testing uses simple linear regression techniques. The results of this research conclude that there is a positive influence between the leadership of the Madrasah Principle on the Quality of Educators at MTsN 1 Bandar Lampung with the correlation between the independent and dependent variables being 0.668. Apart from that, R2 amounts to 0.438 at a significance level of 5%. This means that the contribution of the variable.